2005
DOI: 10.1038/sj.emboj.7600602
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of replication fork progression mediates RNA polII transcription-associated recombination

Abstract: Homologous recombination safeguards genome integrity, but it can also cause genome instability of important consequences for cell proliferation and organism development. Transcription induces recombination, as shown in prokaryotes and eukaryotes for both spontaneous and developmentally regulated events such as those responsible for immunoglobulin class switching. Deciphering the molecular basis of transcription-associated recombination (TAR) is important in understanding genome instability. Using novel plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
262
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(281 citation statements)
references
References 67 publications
(87 reference statements)
19
262
0
Order By: Relevance
“…This effect has been attributed to an enhanced replication block when the transcription machinery is directed toward an oncoming replication fork. Such transcription-dependent replication pause/stall sites have been observed in yeast [17,18] as well as in bacteria [19]. In addition, in E. coli, it has been observed that the manner in which a given DNA lesion is dealt with depends on the direction of replication [20].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This effect has been attributed to an enhanced replication block when the transcription machinery is directed toward an oncoming replication fork. Such transcription-dependent replication pause/stall sites have been observed in yeast [17,18] as well as in bacteria [19]. In addition, in E. coli, it has been observed that the manner in which a given DNA lesion is dealt with depends on the direction of replication [20].…”
Section: Introductionmentioning
confidence: 83%
“…A recent report has demonstrated that the relative orientation of the replication fork with respect to the direction of transcription indeed plays a significant role in transcription-associated recombination in a plasmid-based assay system [17]. This effect has been attributed to an enhanced replication block when the transcription machinery is directed toward an oncoming replication fork.…”
Section: Introductionmentioning
confidence: 99%
“…Although recombination is also enhanced by transcription, the mechanisms underlying transcription-associated recombination may be different from those of TAM. Thus, impairment of replication progression by transcription may be a critical factor triggering transcriptionassociated recombination (43,44), but this is not obvious for TAM. Our study reveals that THO mutations lead to a low hypermutator phenotype in the LAUR system, which is based on a highly expressed lacZ gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The facts that replisome stalling is not normal when RNA polymerase II collides head-to-head with the replisome in the genome and that eukaryotic RNA polymerase II-associated TAR has been reported only for plasmidbased transcription support the existence of such mechanisms (17)(18)(19). In budding yeast, Mec1 checkpoint kinase activity has been shown to be required to prevent so-called ''replication slow zones'' from becoming unstable (20).…”
mentioning
confidence: 99%
“…Transcription-associated recombination (TAR) initiated via collisions of RNA polymerase with the replisome has also been suggested as a potential source of instability for genes transcribed by RNA polymerase II (16,17); however, such encounters between RNA polymerases and the replisome are relatively common occurrences within S-phase of the cell division cycle, so highly effective mechanisms must exist to prevent the generation of recombinogenic lesions. The facts that replisome stalling is not normal when RNA polymerase II collides head-to-head with the replisome in the genome and that eukaryotic RNA polymerase II-associated TAR has been reported only for plasmidbased transcription support the existence of such mechanisms (17)(18)(19).…”
mentioning
confidence: 99%